2012
DOI: 10.1007/s00253-012-4612-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of a new versatile electron transfer system for cytochrome P450-based Escherichia coli whole-cell bioconversions

Abstract: Cytochromes P450 monooxygenases are highly interesting biocatalysts for biotechnological applications, since they perform a diversity of reactions on a broad range of organic molecules. Nevertheless, the application of cytochromes P450 is limited compared to other enzymes mainly because of the necessity of a functional redox chain to transfer electrons from NAD(P)H to the monooxygenase. In this study, we established a novel robust redox chain based on adrenodoxin, which can deliver electrons to mitochondrial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 71 publications
4
59
0
Order By: Relevance
“…For the past few years, we have been engaged in the study of novel P450s from myxobacteria, and some P450s from S. cellulosum So ce56 have shown a potential for industrial and biotechnological applications (Khatri et al, 2010a(Khatri et al, ,b, 2013(Khatri et al, , 2014Ly et al, 2012;Ringle et al, 2013). We were also able to develop an efficient E. coli-based whole-cell bioconversion system for some myxobacterial P450s .…”
Section: Discussionmentioning
confidence: 99%
“…For the past few years, we have been engaged in the study of novel P450s from myxobacteria, and some P450s from S. cellulosum So ce56 have shown a potential for industrial and biotechnological applications (Khatri et al, 2010a(Khatri et al, ,b, 2013(Khatri et al, , 2014Ly et al, 2012;Ringle et al, 2013). We were also able to develop an efficient E. coli-based whole-cell bioconversion system for some myxobacterial P450s .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we first identified efficient autologous redox partners to transfer electrons to the CYP267 family. Although the autologous redox system Fdx8/FdR_B from S. cellulosum So ce56 has already been shown to transfer electrons to myxobacterial CYP109D1, CYP260A1, and CYP264A1 Ringle et al, 2013), the heterologous bovine Adx 4-108 with AdR or the E. coli Fpr has been shown to be more efficient Ringle et al, 2013). However, in this study, the substitution of Adx 4-108 /Fpr by Fdx8/FdR_B showed a significant increase of product yields for drug molecules (Table 1) when using the members of the CYP267 family.…”
Section: Discussionmentioning
confidence: 99%
“…strain CL190 were co-expressed. For in vivo sesquiterpene oxidation by CYP264B1, the heterologous electron-transfer system consisting of Fpr and Adx [57] was used for the co-expression.…”
Section: Resultsmentioning
confidence: 99%
“…The CYP264B1 expression vector pET22b_ CYP264B1 was obtained by cloning the sequence-optimized CYP264B1 gene flanked by restriction sites NdeI and HindIII (Life Technologies) at the same restriction sites into pET-22b (Invitrogen). The vector pETC4oFA was constructed from three fragments: NdeI/HindIII-flanked CYP264B1, EcoRI/HindIII-digested pET_MR8, [57] and NdeI/EcoRI-digested pET-17b.…”
Section: Molecular Cloningmentioning
confidence: 99%